Gastronomic Tourism: Experiencing a Region's Identity through Modern Cuisine in Asia - Syamsul Bahri; Kholilah Yuniar Nasution; Sabrina Wandani Hutabarat; Aulia Risky Harlina (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The culinary diversity in Asia affects the interest of tourists to visit, this is a fascinating thing to explore. This study investigate the role of gastronomy tourism in expressing and communicating the identity of a region. This study use descriptive qualitative method, it explains how to understand research subject phenomena, behavior, perceptions, motivations, actions, and so on, holistically, and how to describe the results in the form of words and sentences (Moleong: 2010). Using the theory of gastronomic identity proposed by Harrington (2005), researchers analyze that Authenticity is the representation of traditional culinary traditions that reflect a region's historical and cultural foundations. Diversity includes the variety of ingredients, recipes, and culinary skills in a region, Innovation is the imaginative modification and advancement of conventional cooking techniques to suit modern preferences and fads. And sustainable food practices prioritize social responsibility and environmental friendliness in the case of five countries in Asia : China, Indonesia, India, Turkey, Kazakhstan. Gastronomy tourism can be found as a powerful tool for promoting a region's identity, both to locals and tourists.